Nutrient enrichment effect on macroinvertebrates in a lowland stream of Argentina - Cortelezzi, Agustina (2015)
One of the most important effects derived from the intensive land use is the increase of nutrient concentration in the aquatic systems due to superficial drainage. Besides, the increment of precipitations in South America connected to the global climate change could intensify these anthropic impacts due to the changes in the runoff pattern and a greater discharge of water in the streams and rivers. The pampean streams are singular environments with high natural nutrient concentrations which could be increased even more if the predictions of global climate change for the area are met. In this context, the effect of experimental nutrient addition on macroinvertebrates in a lowland stream is studied. Samplings were carried out from March 2007 to February 2009 in two reaches (fertilized and unfertilized), upstream and downstream from the input of nutrients. The addition of nutrients caused an increase in the phosphorus concentration in the fertilized reach which was not observed for nitrogen concentration. From all macroinvertebrates studied only two taxa had significant differences in their abundance after fertilization: Corbicula fluminea and Ostracoda. Our results reveal that the disturbance caused by the increase of nutrients on the benthic community depends on basal nutrients concentration. The weak response of macroinvertebrates to fertilization in the pampean streams could be due to their tolerance to high concentrations of nutrients in relation to their evolutionary history in streams naturally enriched with nutrients. Further research concerning the thresholds of nutrients affecting macroinvertebrates and about the adaptive advantages of taxa in naturally eutrophic environments is still needed. This information will allow for a better understanding of the processes of nutrient cycling and for the construction of restoration measures in natural eutrophic ecosystems.